ALTERNATIVE ENERGY SOURCES - S.N.Khashimova; A.A.Abdikarimova (Scholar Express Journals, 2024)
This article presents alternative energy sources and their pros and cons, as well as goals for the transition to renewable energy sources in countries around the world. In addition, a number of measures on the effective use of renewable energy sources in our republic have been highlighted
Keywords: Alternative energy; hydropower; wind energy; solar energy